Actuele Picturale Expressies 2 : Gele Zaal, 16.11.85 - 05.01.86. - Claus, Joos; Rau, Daan; Gele Zaal, Gent (Gent : Noordstarfonds vzw, 1985)
Demuynck, Emmanuel ; Eerdekens, Fred ; Gentils, Frans ; Voordeckers, Jurgen
Gele Zaal, Gent, 16/11/85 tot 5/01/86
kunstcatalogus